PENGARUH AKUNTABILITAS, FAKTOR ORGANISASIONAL, DAN PENGGUNAAN SISTEM PENGUKURAN KINERJA TERHADAP KINERJA ORGANISASI - Sari, Martdian Ratna (UI Scholars Hub, 2016)
This study aimed to examine the effect of accountability, organizational factors, and the use of performance measurement system on organizational performance, particularly educational organizations in the form of private Catholic universities. Mixed method with sequential explanatory strategy is used in this study to collect and to analyze data. In the quantitative stages, data from 159 respondents of upper-level and mid-level managers at Catholic universities is collected through questionnaire and is then analyzed using SEM-PLS. Furthermore, content analysis technique was used to analyze transcript of interview in the qualitative stages. The results indicate that there is an effect of accountability and a clear and measurable perception of goals on the improvement of university’s performance. This study has practical implications in supporting the government to create a system of accountability and good governance for universities. For private Catholic universities, this research shows that regulations or legislations required by the government are factors that encourage improvement of performance and governance of universities. For the association coordinating private Catholic universities (APTIK), this study can be a reference in developing and strengthening cooperation among the private Catholic universities.